The impact of a mental training program on developing some basic football skills for students - Kazar, Asst. L. Ashraf Jaafar (Sulaimani Journal for Humanities, 2026)
The science of sports training is one of the most important sciences in the field of sports, as it aims to gradually prepare individuals to endure rigorous athletic training and maintain that endurance. Physical conditioning is one of the most important elements of success in football, and it is the starting point for achieving top athletic levels. Furthermore, physical conditioning is considered one of the most important pillars upon which a football player's ability to perform at a high level in matches is based. Specific physical conditioning aims to develop and refine the essential physical attributes characteristic of football, working to maximize their potential so that the player can reach the highest level. This involves placing the trainee or player in conditions similar to competitive situations, but with a level of endurance closer to or slightly higher than that required for competition in all sports, as well as for withstanding psychological and physical pressures. It also takes into account their physical capabilities and functional requirements.
Keywords: Mental training; basic skills; with football